Die ontstaan van die Samaritane: "n Kritiese herbesinning - Venter, J. G. H. (Hervormde teologiese studies, 1989)
The origin of the Samaritans re-examinedThe traditional approach to the study of the origins of the Samaritans as a group or a nation usually takes 2 Kings 17 to be a description of their origin. The aim of this article is to show that there is little or no evidence in 2 Kings 17 pointing in this direction. Several factors in history and in ancient literature make it almost impossible to come to any definite conclusion as to the origin of the Samaritans as they are known to us in the New Testament.